Islamic Schooling in the West Pathways to Renewal (Springer International Publishing, 2018)
This book presents the views of leading scholars, academics, and educators on the renewal of Islamic schools in the Western context. The book argues that as Islamic schools in Western contexts have negotiated the establishment phase they must next embrace a period of renewal. Renewal relates to a purposeful synthesis of the tradition with contemporary educational practice and greater emphasis on empirical research substantiating best practices in Islamic schools. This renewal must reflect teaching and learning practices consistent with an Islamic worldview and pedagogy. It should also inform, among other aspects, classroom management models, and relevant and contextual Islamic and Arabic studies. This book acquaints the reader with contemporary challenges and opportunities in Islamic schools in the Western context with a focus on Australia.